Stress fractures: a diagnostic problem. Issue 8 (August 1987) - Waisman, Y; Varsano, I; Grunebaum, M; Mimouni, M
Abstract : Three cases of stress fracture, in which diagnosis was aided by sequential radiographs and radionuclide scanning are presented; and a procedure for their management, which attempts to eliminate the need for invasive investigations, is suggested.